KOMITMEN ORGANISASIONAL SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN PESANTREN - Akmal Mundiri (Nurul Jadid University, 2015)
Changes in the educational institutions of Islam which is a positive response to the modernist Muslims against Muslims backwardness of modern Western advances. Efforts renewal and modernization of Islamic education is done by improving the quality of education which according to V. Gasparez include keterwujudan, reliability, kecepattanggapan, assurance, and empathy. Quality improvement in schools necessitates the commitment of human resources education that participated memuncukan productive work ethic. The commitment of human resources education in schools aimed at improving the quality of education embodied in the form of affective commitment in the form of an emotional attachment educators as well as education and awareness normative commitment in the form of individual educators of their responsibilities.